#TITLE_ALTERNATIVE# - RAMADHAN UTAMA (NIM 15107037); Pembimbing: Dr. Deni Suwardhi, ST, MT., dan Ir. Agoes Soewandit, IHSAN
Mining jobs demand speed and accuracy on every measurement. In PT. Weda Bay Nickel, each stockpile has maximum limit of mass and volume value. If the stockpile has reached the maximum limit, a new stockpile should be made to store the minerals. The current measurements the mass of the stockpile is only done by weighing-machine. However there are still errors on the weighing-machine such as not functioning and error recording data. therefore required new methods to determine the mass and volume of the stockpile quickly and accurately. Close range photogrammetry (CRP) can provide data in the form of point cloud. Point cloud is a set of points that have the coordinates that results from the processing of two overlap photos. The point cloud data can be processed to get a digital elevation model data (DEM) that can used to measuring the volume of the object.from the volume and specific weight data, the mass of the object can be calculated. CRP may be combined with the unmanned aerial vehicle (UAV) in terms of data acquisition. with the help of UAV, the data acquisition can be done quickly and able to obtain the top of the object data. So the CRP method can be an alternative method of calculating the volume of the stockpile quickly and accurately.